THE RELATIONSHIP BETWEEN THE OPENNESS OF EXPERIENCE AND THE SEMANTIC-LIFE ORIENTATION OF STUDENTS - Севост`янов, Павло Олександрович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article considers the concept of openness of experience within the framework of the model of the Great Five. The phenomenon of sense-orientation of the personality is analyzed; the role of openness of experience and sense-orientation in the life of the individual was discussed; features of the structural organization of individual experience are presented. Theoretically, the content of the personal component of the individual experience is researched. The theoretical substantiation of the study of the relationship between the openness of experience and the sense-life orientation of the students is conducted. An empirical study was conducted on a sample of 154 students. The differences in the indicators of openness of experience and sense of orientation in the students of the Slavic national university and the V.N. Karazin Kharkiv National University are considered, as well as students of technical and humanitarian specialties. The relationship between the openness of experience with different parameters of the resin of sense-life orientations has been revealed.